PENGARUH PENAMBAHAN SERAT IJUK TERHADAP KUAT TARIK BELAH BETON DENGAN FAKTOR AIR SEMEN 0,5 - Angga Ongky Perdana; Ade Sri Wahyuni; Elhusna Elhusna (Universitas Bengkulu, 2019)
The advantages of concrete are : high in compressive strength, durable, easy to cast. The weakness of concrete is low in tensile. Palm fiber is the natural fiber which is high in tensile. This research aims to know the tensile strength of concrete with palm fiber addition. The diameter of the cylinder is 15 cm and 30 cm height. There are 4 variation in palm fiber addition i.e 2,5%, 5%, 7,5% and 10%. The concrete mix design is based on SK SNI-T-15-1990-03 with water cement ratio 0,5 and slump range between 6-10 cm. The curing process in based on SNI03-2493-2011. The test was done at the age of 28 days based on SNI 03-2491-2002. The highest value of tensile strength test is with 10% addition of palm fiber (2,667 MPa) which is 24,09% higher than normal concrete. This research shows, the palm fiber addition increase the tensile strength of concrete.